Meninjau Peranan Text Mining sebagai Alat Strategis dalam Industri Kreatif melalui Sajian Webinar - Hakim, Lukmanul; Peryanto, Ari; Susanto, Dwi; Fitri Widodo, Yuwono (LPPM Universitas Harapan Bangsa Purwokerto, 2025)
The growth of unstructured data has been triggering a big data explosion. About 90 percent of the current unstructured data has not been fully analyzed so that cannot be used for valuable new information. Text mining can process text data to be extracted into new knowledge, identify significant patterns, and find hidden correlations. The use of text mining can be applied to various themes such as encouraging creativity in industry, society, and researchers by focusing on exploration versus exploitation strategies in crowdsourcing contests by utilizing data from proposals to make close and distance classifications between proposals, analyze sentiment tone on product launch announcements or creative economy programs and make correlations with sales data or public interest in a post-launch program, performing software lifecycle management by leveraging new ideas from users/customers such as Google reviews to create clusters of topics discussed in the comment section, and combining a topic-search approach and language style that can make a successful Kickstarter campaign. In this article, the author discusses the definition, process, application, and integration of text mining in the context of encouraging the creative industry to innovate further.